(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2011)
Jacques Derrida’s critique of philosophical origins, in his essay on Plato and elsewhere, unveils a sacrificial dynamic that René Girard hypothesizes as the origin of human culture. Girard’s latest book, Achever Clausewitz (2008), applies his mimetic theory to history: the Prussian general’s analysis of increasingly violent «reciprocal action» in modern, post-revolutionary warfare exposes the mimetic principle of lethally violent doubles. This «trend to extremes» works to the dissolution of institutions – national sovereignty, international law, politics, war itself – that Derrida explores in Voyous, his book-length essay on terrorism (2003). Both authors see the world of globalized commerce and the globalized terrorism that goes with it as enmeshed in violent undifferentiation. Girard’s historically grounded work supplies a narrative line to Derrida’s structural analyses. Derrida’s call for an ever more vigorous deconstructive rationality as a solution is symptomatic of philosophy’s blindness to the interactive crescendos of human violence that is unveiled in Girard’s religious anthropology.